Keyhole approach in the neuroendoscopic treatment for hydrocephalus. Issue 1 (January 2017) - Cai, Qiang; Zhang, Xiangyang; Wang, Long; Huang, Shulan; Chen, Zhibiao; Chen, Qianxue
Abstract : Abstract: The aim of the study was to explore keyhole approach and dura suture in the neuroendoscopic treatment for hydrocephalus. Twelve cases of hydrocephalus patients who were treated with neuroendoscope by this approach were analyzed retrospectively from April 2015 to April 2016 in our department. The basic steps of this procedure was using drill and milling cutter to form a small bone flap instead of burr hole, and then making a cruciate incision on the dura. After endoscopic third ventriculostomy or endoscopic third ventriculostomy + ventriculocystostomy finished, dura was sutured and the bone flap was reset. All 12 patients could suture dura effectively, and no cerebrospinal fluid leak and subcutaneous cerebrospinal fluid collection happened; symptoms of hydrocephalus were also improved. Moreover, during the operation, we found this approach could suspend dura, and avoid the cerebral sulcus and cortical coarse vein effectively, which could reduce the risk of intracranial hemorrhage. In addition, we found this approach could increase the reachable range of the neuroendoscope significantly. Keyhole approach can suture dura and avoid the cerebral sulcus and cortical coarse vein effectively, increase the indications, and reduce complications of neuroendoscope. So, this approach has clinical values and can be used in hydrocephalus.